Economic effects of cattle meat production of different genetic provenience in mountainous areas of Northern Kosovo and Metohia - Spasić, Zvonko; Milošević, Božidar; Stolić, Nikola; Lalić, Nebojša; Jašović, Boban (Economics of Agriculture, 2010)
In this research we examined the influence of two different genotypes (Simmental and crossbreed of Simmental and busa) on: weight gain(y), feed consumption for weight gain(x) per month during the fattening period average productivity (A. P.), represented by relation of total weight gain and consumed nutritive units, marginal weight gain (M.G.), which represents ratio of increased weight gain and increased input of nutritive units, as well as weight gain elasticity for achieved production level i. e. ratio of proportional weight gain increment and proportional increment of nutritive units during the fattening period. Fattening results show that cross-breed F1 achieved lower daily weight gain for 11,24% and higher feed consumption per growth unit (7,041 : 5,975) than Simmental cattle. Average productivity has a benefcial trend in Simmental cattle in comparison with cross-breed F1 generation. Coeffcient of correlation among feed and weight gain during the fattening period in cross-breed was 0,733, while in Simmental breed it was 0,569. The achieved economic effects of fattening are a consequence of genetic predisposition of genotypes investigated, since fattening process evolved in identical conditions, so that non-genetic variance could be conditionally neglected.